Offshore wind energy generation : control, protection, and integration to electrical systems - Anaya-Lara, Olimpo; Campos-Gaona, David; Moreno-Goytia, Edgar Lenymirko; Adam, Grain Philip (Chichester, West Sussex : John Wiley & Sons Inc., 2014)
Equipping electrical engineers for the engineering challenges in utility-scale offshore wind farms, this important reference sets out the fundamentals and latest innovations in electrical systems and control strategies deployed in offshore electricity grids for wind power integration. --
7.4 Energy Storage Systems (EESs)7.5 Fault Current Limiters (FCLs); 7.6 Sub-Sea Substations; 7.7 HTSCs, GITs and GILs; 7.8 Developments in Condition Monitoring; 7.9 Smart Grids for Large-Scale Offshore Wind Integration; Acknowledgements; References; A: Voltage Source Converter Topologies; A.1 Two-Level Converter; A.2 Neutral-Point Clamped Converter; A.3 Flying Capacitor (FC) Multilevel Converter; A.4 Cascaded Multilevel Converter; A.5 Modular Multilevel Converter; References; B: Worked-out Examples; Exercise 1; Exercise 2; Exercise 3; Exercise 4; Exercise 5; Exercise 6; Index
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Wind power plants; Offshore electric power plants; Wind energy conversion systems; TECHNOLOGY & ENGINEERING -- Mechanical; Offshore electric power plants; Wind energy conversion systems; Wind power plants; Electronic books; Electronic books